Amylase creatinine clearance ratio after biliary surgery. - Donaldson, L A (1977)
The amylase creatinine clearance ratio (ACCR) is considered to be a more sensitive index of acute pancreatitis than the serum amylase level. Serial ACCR estimations were undertaken in 25 patients undergoing an elective cholecystectomy. Using accepted criteria, 28% of these patients developed, in the postoperative period, biochemical evidence of pancreatic gland damage, although the serum amylase level remained normal. This raised ACCR was particularly noted in patients who had undergone an exploration of the common bile duct. The ACCR would appear to be a more sensitive index of pancreatic gland disruption secondary to biliary surgery than the serum amylase level.